Scenario Planning of Urban Gendered-Development in Surabaya - Mochamad Kevin Romadhona; Rachmat Dimas Oktafenanda (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2026)
This study investigates the development of gender equality in Surabaya by analysing the Gender Development Index (GDI) from 2020 to 2023 and projecting its trajectory until 2025. Employing a quantitative-descriptive approach, the research utilises secondary data obtained from Badan Pusat Statistik Surabaya and applies linear regression analysis to examine trends in gender equality across the dimensions of health, education, and economic achievement. The findings demonstrate a consistent increase in the GDI, from 93.58 in 2020 to 95.56 in 2023, reflecting gradual progress toward gender parity despite the persistence of disparities between men and women, particularly in income distribution and political participation. The regression model further predicts continued improvement, with projected GDI values reaching 96.17 in 2024 and 96.86 in 2025. The novelty of this study lies in its integration of statistical trend analysis with a gender-governance perspective to evaluate not only numerical progress but also the structural challenges underlying gender inequality in an urban Indonesian context. This research contributes to the discourse on gender mainstreaming by providing empirical projections of gender equality at the municipal level and offering policy-oriented insights for strengthening gender-responsive governance in support of the achievement of Sustainable Development Goal 5 on gender equality by 2030.